Ensino de botânica na educação básica: material de apoio ao educador utilizando PANC - Zerpa, Elisama Martins (Universidade Federal de São Carlos, 2022)
As many aspects of education, teaching botany may not be easy due to several factors and awakening the student's interest in learning about plants can be very difficult. In this work we aim to help the teacher with support material so that he can present some plants in a different way, through cooking, with practical experiences, and showing students the wide variety of unconventional food plants that exist. The material has information on conventional food plants (PAC) and unconventional food plants (PANC), with a focus on PANC, where it will be possible to learn where to find, how to identify, how to collect, what are the benefits in food, forms of cultivation and examples of consumption. Videos of very practical cooking recipes were produced, which the teacher can make together with the class or take ready-made so that the students have the opportunity to taste. This support material can be used when the teacher starts to teach Botany or after the students already have knowledge about basic concepts, in that case, the material would offer elements that reinforce the concepts and help to have greater contact with plants.
Botany teaching in basic education: support material for teachers using unconventional food plants
Keywords: Ensino de botânica; PANC; Alimentação vegetal diversificada; Material de Apoio em Botânica; Teaching botany; Diversified plant food; Support material in botany; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO